THE EFFECT OF RHIZOBIUM-BASED BIOFERTILIZER AND PHOSPHORUS APPLICATION ON THE GROWTH AND YIELD OF PEANUT PLANTS ON ACIDIC SOILS - Maylani Lucky; Laurensius Tobing; Kristianus Heri Hartanto (Innofarm : Jurnal Inovasi Petanian, 2026)
Peanut (Arachis hypogaea L.) is an important food crop with high economic value; however, its productivity in Indonesia, particularly in West Kalimantan, remains relatively low due to the dominance of acidic soils with limited nutrient availability. This study aimed to determine the effects of Rhizobium-based biofertilizer and phosphate fertilizer application on the growth and yield of peanut plants grown on acidic soils, as well as to identify the best combination of treatments. The research was conducted in Sekadau Hilir District, Sekadau Regency, West Kalimantan, from August to November 2025. A factorial Completely Randomized Design (CRD) was employed with two factors, namely Rhizobium doses (0, 50, 100, 150, and 200 g per plant) and phosphate fertilizer doses (0, 2.5, and 5 g per plant), with four replications. Observed variables included plant height, number of branches, days to flowering, number of pods, pod weight, and number of seeds. Data were analyzed using analysis of variance (ANOVA), followed by the Honestly Significant Difference (HSD) test at the 5% significance level when significant effects were detected. The results showed that the application of Rhizobium, phosphate fertilizer, and their interaction had significant to highly significant effects on plant height, days to flowering, number of pods, pod weight, and number of seeds, but had no significant effect on the number of branches. The combination of Rhizobium at a dose of 200 g per plant and phosphate fertilizer at a dose of 5 g per plant produced the best growth and yield performance of peanut plants. Therefore, the combined use of Rhizobium-based biofertilizer and phosphate fertilizer has strong potential to improve peanut productivity on acidic soils in a sustainable manner.